2014
DOI: 10.4067/s0718-19572014000300008
|View full text |Cite
|
Sign up to set email alerts
|

Azadinium (Amphidomataceae, Dinophyceae) in the Southwest Atlantic: In situ and satellite observations

Abstract: Resumen.-Los azaspirácidos (AZAs) son toxinas identificadas en invertebrados marinos y tienen amplia distribución geográfica, no reportadas aún en Argentina ni Uruguay. Aunque el primer agente causal identificado es el dinoflagelado fotosintético Azadinium spinosum, diversos estudios indican que otras especies sintetizan asimismo AZAs. Recientemente se ha detectado la presencia de A. cf. spinosum en el Atlántico Sudoccidental y la generación de dos extensas floraciones como nuevos eventos a escala global. En e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…spinosum occurred in spring at low water temperature (< 10 8C), Azadinium spp. at the coastal station was recorded during the warm periods in summer and autumn as well (Akselman et al, 2014) which might indicate the presence of several species of Azadinium with different ecological requirements in Argentinean waters.…”
Section: Field Situationmentioning
confidence: 93%
See 4 more Smart Citations
“…spinosum occurred in spring at low water temperature (< 10 8C), Azadinium spp. at the coastal station was recorded during the warm periods in summer and autumn as well (Akselman et al, 2014) which might indicate the presence of several species of Azadinium with different ecological requirements in Argentinean waters.…”
Section: Field Situationmentioning
confidence: 93%
“…A more detailed investigation on the seasonal and interannual variability of Azadinium spp. conducted at a fixed station close to the Argentinean coast (Akselman et al, 2014) from 1994 to 2000 revealed Azadinium to be present in all years but in low abundance and sporadically. Nevertheless, whereas the offshore blooms of A. cf.…”
Section: Field Situationmentioning
confidence: 99%
See 3 more Smart Citations